Hybrid Neutrals : Modes of Abstraction and the Social - Collins, Tricia; Milazzo, Richard; Indiano, Gary; The University of North Texas Art Gallery, Denton; The J.B. Speed Art Museum, Louisville; Alberta College of Art Gallery, Calgary; The Contemporary Arts Center, Cincinnati; Richard F. Brush Art Gallery, St. Lawrence University, Canton; Santa Fe Community College Art Gallery, Gainesville (New York : Independent Curators Incorporated, 1988)
Alexander, Vikky ; Armleder, John M. ; Bender, Gretchen ; Bleckner, Ross ; Cemin, Saint Clair ; Charlesworth, Sarah ; Diao, David ; Gober, Robert ; Halley, Peter ; Hsu, Tishan ; Koons, Jeff ; Lasker, Jonathan ; Lemieux, Annette ; McCollum, Allan ; Nagy, Peter ; Otterson, Joel ; Steinbach, Haim ; Stephan, Gary ; Taaffe, Philip ; Vaisman, Meyer ; Welling, James
Hybrid Neutrals : Modes of Abstraction and the Social, The University of North Texas Art Gallery, Denton, August 29 - September 30, 1988 / The J.B. Speed Art Museum, Louisville, November7, 198 - January 2, 1989 / Alberta College Gallery of Art, Calgary, February 9 - March 9, 1989 / The Contemporary Arts Center, Cincinnati, March 31 - May 6, 1989 / Richard F. Brush Art Gallery, St. Lawrence University, Canton, October 12 - November 15, 1989 / Santa Fe Community College Art Gallery, Gainesville, February 4 - March 18, 1990
boek